The Book of Ben Sira in Hebrew : a text edition of all extant Hebrew manuscripts and a synopsis of all parallel Hebrew Ben Sira texts - Beentjes, Pancratius Cornelis. (Vetus Testamentum, Supplements, 1997)
This volume deals with the Hebrew texts of all nine manuscripts discovered between 1896 and 1982 of the Book of Ben Sira that is reckoned among the deuterocanonical biblical wisdom literature and was written in Jerusalem about 180 BCE. In the first part of this volume the Hebrew manuscripts are offered in facsimile, id est presenting the real textual state of the recovered texts. The second part of this volume offers in a more convenient and functional way than in former text editions a synopsis of all Hebrew Ben Sira texts which are available in more than one manuscript.